Impact of virtual continued medical education on carbon footprint and awareness of digital sobriety: A retrospective cross-sectional study among public health professionals in India - Gandhi, Aravind P.; Padhi, Bijaya Kumar; Goel, Kapil; Singh, Amarjeet; Kansal, Om Prakash; Al-Ahdal, Tareq (Frontiers in Public Health, 2023)
Background Due to the COVID-19 pandemic, physical meetings and continuing medical education (CMEs) are being conducted in virtual mode. Digital sobriety has been advocated as a strategy for controlling the environmental emission from online events. The present study was undertaken to assess the impact of virtual CMEs on the environment and the participants' perception, knowledge, attitude, and practices of digital sobriety during the CMEs. Methods A retrospective cross-sectional Google form-based online study was conducted among the 1,311 registrants of 23 virtual CMEs hosted in India. A pre-tested English questionnaire was used to collect the data. The potential carbon footprint of the significant physical CME activities and the carbon emission (CE) of the virtual CMEs were estimated. Among the registrants contacted, 251 consented and participated in the study. Results The CE of the virtual CMEs was 0.787 metric tons of carbon dioxide equivalent (MT CO2 Eq). If the CMEs were conducted physically, the potential CE was estimated to be 290.094 MT CO2 Eq. The awareness rate of digital sobriety was 35%. Most of the participants (58.7%) from the current study preferred the hybrid mode of CMEs. Conclusions Virtual, digitally sober CMEs have reduced the potential CE by 99.7% compared to physical CMEs in India. The awareness and knowledge about digital sobriety is low in India. Knowledge, networking, social interactions, and overall satisfaction were relatively lower in the virtual mode of CMEs than in the physical mode.